2009
DOI: 10.1007/s10633-009-9208-3
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal hyperoxia and the developing rat retina: beyond the obvious vasculopathy

Abstract: Although a great deal of emphasis has been placed on the vasculopathy that is associated with oxygen-induced retinopathy (OIR), our studies also revealed significant and irreversible structural (retinal histology) and functional (scotopic and photopic electroretinograms) impairments that were significantly more severe in pigmented Long-Evans rats compared to the more commonly used albino Sprague Dawley rats. In the following pages, we will highlight what we have learned about the retinal pathophysiological pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 19 publications
2
11
0
1
Order By: Relevance
“…13, 17, 18 It also has been shown that hyperoxia causes neuronal death in brain 19 and retina. 24 Hence, it is important to investigate retinal cell death in the OIR retina during the hyperoxic phase. In the present study, we analyzed hyperoxia-induced retinal apoptosis using terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL) assay (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13, 17, 18 It also has been shown that hyperoxia causes neuronal death in brain 19 and retina. 24 Hence, it is important to investigate retinal cell death in the OIR retina during the hyperoxic phase. In the present study, we analyzed hyperoxia-induced retinal apoptosis using terminal deoxynucleotidyl transferase (TdT) dUTP nick-end labeling (TUNEL) assay (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%
“…21, 22, 23 Hyperoxia-induced defects in retinal neural function have been reported in neonatal rats. 24 …”
mentioning
confidence: 99%
“…The inner retina has long been considered to be the primary region affected in human ROP and animal models. 42 Lately, dysfunctions of photoreceptors are detected in a significant number of older children formerly afflicted with ROP; these outer retinal dysfunctions are composed of defective dark adaptation because of rod dysfunction, 3 abnormal cone function, 43 and retinal depigmentation. 44 Moreover, the apparent progressive nature of these changes is suggested.…”
Section: Discussionmentioning
confidence: 99%
“…The oxygen‐induced retinopathy (OIR) mouse model is the most widely used animal model to study ischemic neovascular retinopathies including retinopathy of prematurity and late neovascular proliferative diabetic retinopathy (Smith et al ; Stahl et al ). As in human ischemic retinopathy patients, retinal function is markedly impaired in OIR mice (Stahl et al ; Dorfman et al ; Vessey et al ; Ridano et al ; Matsuda et al ). Moreover these mice also exhibit reduced numbers of dopaminergic amacrine cells (Spix et al ) and delayed intermediate vascular plexus formation (Ritter et al ; Spix et al ).…”
mentioning
confidence: 99%